Through the medicine cabinet - Greenburg, Dan.; Davis, Jack E. (London : McMillan Children's Books, 1988)
After Zack opens his medicine cabinet one morning and sees a boy who could be his double staring back at him, he enters a parallel universe.
Keywords: Supernaturel -- Fiction